Preparation, characterization, and drug release properties of poly(2-hydroxyethyl methacrylate) hydrogels having beta-cyclodextrin functionality - OGAN, AYŞE; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (JOHN WILEY & SONS INC, 2008)
A new beta-cyclodextrin urethane-methacrylate monomer was synthesized from the reaction of toluene-2,4-diisocyanate, 2-hydroxyethyl methacrylate (HEMA), and beta-cyclodextrin (beta-CD). Based on inclusion character of beta-CD, a series of hydrogels were prepared by irradiating the mixtures of beta-cyclodextrin urethane-methacrylate monomer (beta-CD-UM), poly(ethylene glycol) diacrylate (PEG-DA), HEMA, and the photoinitator. Gel percentages and equilibrium swelling ratios (%) of hydrogels were investigated. It was observed that the equilibrium-swelling ratio increased with increasing beta-CD-UM content in the hydrogel composition. SEM images demonstrated that beta-CD-UM based hydrogel have porous fractured surface. In this study four different drug molecules, salicylic acid, sulfathiazole, rifampicin, and methyl orange as model drug, which are capable of forming inclusion complexes with beta-CD were chosen. For sulfathiazole and rifampicin, the drug loadings are very low (0.04 and 0.008 mmol/g dry gel), whereas methyl orange and salicylic acid drug uptakes are found as 0.15 and 0.18 mmol/g dry gel, respectively. The incorporation of beta-CD-UM comonomer into the gel slightly reduces the methyl orange and salicylic acid releases. However, a significant enhancement was achieved in the case of sulfathiazole delivery. It can be concluded that the inclusion complex formation capability of beta-CD moiety increases the drug release by improving the aqueous solubility of hydrophobic drugs. On the other hand, in the case of hydrophilic drugs, the drug release retards by forming strong drug-beta-CD complex and reducing the drug diffusivity. (C) 2008 Wiley Periodicals, Inc.
Keywords: beta-cyclodextrin; photoinitiation; drug release; inclusion complex; hydrogel; PHARMACEUTICAL APPLICATIONS; INCLUSION COMPLEXES; ALPHA-CYCLODEXTRIN; DELIVERY; SOLUBILIZATION; MICROSPHERES; COPOLYMERS; SYSTEM